Physical and psychosocial problems in cancer survivors beyond return to work: a systematic review. Issue 5 (23rd December 2013) - Duijts, Saskia F. A.; van, Martine P.; Spelten, Evelien; van, Peter; Anema, Johannes R.; van der, Allard J.
Abstract Objective Attention for the expanding group of cancer survivors at work, and the late effects they are confronted with while working, has been limited. The objective of this systematic review is to identify and summarize studies, exploring ongoing physical and/or psychosocial problems related to functioning of employees with a history of cancer, beyond their return to work. Methods Publications were identified through computerized Medline, Psychinfo, Embase, and Cinahl searches (January 2000‐March 2013). Studies had to be directed at cancer survivors, who were employed during the study. Both qualitative and quantitative studies were included. Quality assessment of these studies was performed. Two reviewers independently extracted data from each publication, e.g., physical and/or psychosocial problems (e.g., fatigue and cognitive limitations), outcome measures (e.g., work productivity), and qualitative and quantitative results. Results The search identified 8979 articles. After exclusion on title and abstract, 64 were retrieved for full text screening, of which 30 met the inclusion criteria. A total of 20 studies reported quantitative and 10 studies reported qualitative results. The majority of studies assessed psychosocial problems in cancer survivors at work. Cognitive limitations, coping issues, fatigue, depression, and anxiety were reported to influence work ability. Physical problems, such as difficulties with lifting and treatment‐induced menopausal symptoms, were frequently described to affect functioning at work. Conclusions Ongoing physical and/or psychosocial problems are present in occupationally active cancer survivors, which may cause serious difficulties at work. The results of this study may be used as input for developing supportive interventions for these survivors. Copyright © 2013 John Wiley & Sons, Ltd.